Prototype of Automatic Sorting of Goods in Cosmetics Warehouse - Aliim Muqaffi Siswanto; Muchlas Muchlas (Buletin Ilmiah Sarjana Teknik Elektro, 2022)
One of the tasks of the warehouse as a vital support unit for the distribution process and inventory of goods is sorting. Especially for cosmetic warehouses. Product sorting in warehouses so far is still done manually which can cause negligence and take time when collecting stored product data. A storage system is the process of placing and acquiring goods and products to and from a specific location within an industrial plant or warehouse. To solve this problem, the warehouse needs an automatic sorting tool. This allows employees to easily record products stored in warehouses without using a large number of staff. The method applied to this tool is microcontroller-based automation which includes hardware design in the form of conveyor design, flow charts, and board layouts. Software design includes listing code, block diagram explanations and system flowcharts. Testing system working tools such as barcode scanning, servo angle, infrared sensor and conveyor. The items used as experimental samples totaled 9 pieces with the categories of facial wash, lipstick, and shampoo. Based on the tests that have been carried out, the prototype of automatic sorting of goods is already working as expected.